Editorial: Lifestyle intervention approaches in prediabetes or diabetes - Moser, Othmar; Kaser, Susanne; Sourij, Harald (Frontiers in Endocrinology, 2024)
In the therapy and treatment of diabetes mellitus, physical activity, exercise and nutrition play an important role to improve disease-specific outcomes (1)(2)(3). In previous research it was shown that those with type 1 diabetes, who are more physically active face lower risk of overweight, obesity and hypertension when compared against their physically inactive counterparts (4). Furthermore, even a short-term moderate-intensity endurance training program was shown to ameliorate glycated hemoglobin (HbA1c) levels and functional capacity (5). At the same time, physical activity and exercise increase the risk of acute and post-exercise hypoglycemia (6) based on different pathophysiological factors (7), hindering people with type 1 diabetes to engage in regular physical activity due to the fear of glycaemic disturbances (8).In people with type 2 diabetes, physical activity and exercise where shown to improve glycaemia (9), decrease the risk of complications and comorbidities (1). Furthermore, in